Tuktoyaktuk. Ultra high resolution orthomosaic - Gonçalo Vieira; Pedro Pina; Dustin Whalen; Pedro Freitas; Daniel Pinheiro; François Malenfant; Paul Fraser; Angus Robertson; Heather B. Berry (Zenodo, 2020)
Aerial orthomosaic of the hamlet of Tuktoyaktuk - Poster A0. Survey conducted in July/August of 2018 and 2019 using a Sensefly ebee and a Sensefly ebee RTK Plus. Spatial resolution 10 cm.